Building Visit Intention to Local Destination Panorama Pabangbon through Electronic Word-of-mouth (eWOM) and Visitors’ Trust - Wendry Sudarsono; Fatimah Abdillah; Nurtiah Nurtiah; Egi Adithia Pradana (ProBisnis : Jurnal Manajemen, 2023)
The tourism sector has developed into an industry that has an essential role in economic growth in the world. Even though the tourism sector was most affected during the Covid-19 crisis, tourism potential needs to continue to receive support, especially in the recovery and development process, especially local tourism. Tourists will be excited to visit a destination that has credibility and popularity. Based on the ease of access to information via the Internet, potential tourist destinations will receive a good assessment in the form of electronic word-of-mouth (eWOM). This study aims to determine the process of the two factors that form the tourist's intention to visit a local tourist attraction. This quantitative research is conducted based on the perceptions of 130 tourists who had no experience visiting these attractions. Respondents to this study have also seen information about this local tourist attraction through an online platform. Data is processed using SPSS. The results showed that eWOM and trust increase tourist interest in visiting. This research provides theoretical and practical advice.